Proteomics Analysis of Myocardial Tissues in a Mouse Model of Coronary Microembolization - Chen, Ao; Chen, Zhangwei; Xia, Yan; Lu, Danbo; Jia, Jianguo; Hu, Kai; Sun, Aijun; Zou, Yunzeng; Qian, Juying; Ge, Junbo (Frontiers in Physiology, 2018)
Coronary microembolization (CME) is an important clinical problem and it is related to poor outcome. The specific molecular mechanisms of CME are not fully understood. In the present study, we established a mice model of CME. Isobaric tags for relative and absolute quantitation (iTRAQ) and liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS) technologies identified 249 differentially expressed proteins in the myocardial tissues of CME mice as compared with sham-operated mice. Bioinformatics analysis demonstrated that these differentially expressed proteins were enriched in several energy metabolism or cytoskeleton organization related processes or pathways. Quantitative PCR and Western blotting validation experiments revealed that succinate dehydrogenase (SDHA and SDHB) were upregulated, Rho GDP dissociation inhibitor α (RhoGDIα) and Filamin-A (FLNA) were downregulated significantly in CME mice. These ﬁndings indicated that the alternations of the cytoskeleton and energy metabolism pathways play important roles in the pathogenesis of CME, future studies are warranted to verify if targeting these molecules might be useful to alleviate CME injury or not.